The Impact Of Social Media On Animation Creativity Through Intrinsic Motivation Among University Students In Jiangsu Province, China - Wang, Lei (2024)
Social media has emerged as a powerful medium of communication across the globe, and its extensive use has changed the way people communicate and interact online. We have reached the point where these tools are no longer optional but instead integral components of effective 21st-century school leadership. In recent years, interest in creativity has grown as the field of education has placed greater emphasis on the expression of creativity. Meanwhile, studies have shown that the creative thinking skills required by animation students are declining. It can be seen that attention on social media has increased while students’ creativity has decreased. Preliminary research has shown that social media has an impact on students’ creativity, and intrinsic motivation plays an important role in it. The study combines the theory of stimulus-organization-response (S-O-R). Students receive stimulation (S) in the form of exposure to social media, and as organisms (O), this stimulation affects their creative motivation, resulting in responses (R) that affect students’ creativity. In the study, a theoretical framework for the impact of social media on students’ creativity under the influence of intrinsic motivation was established, and the development of hypotheses was completed. The study also measures the relationship among social media, intrinsic motivation, and students’ creativity, as well as influence effects. The research used quantitative research measured by survey research and quasiexperimental methods.